Pengembangan Media Pembelajaran Fisika Berbasis Android dengan MIT App Inventor pada Pokok Bahasan Fluida Statis - Yuli Yanti; Neng Nenden Mulyaningsih; Riskiono Slamet (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The existence of mobile learning-based learning media on the Android platform can make knowledge spread faster and not be limited by space and time. The existence of mobile learning is very much needed in the digital era as it is today, therefore this study aims to develop an android-based physics learning media with the MIT APP Inventor on the subject of static fluids. The research method used in this research is the research and development method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) which in this study was carried out to the Implementation stage. The learning media innovation that was developed was named EduPhysics, the output produced in the form of an Android-based learning application that can be accessed offline. This mobile learning has also been said to be feasible by experts based on the assessment of the validation results of media experts, material experts, and linguists, with average scores of 87%, 94%, and 87.5%, respectively. Based on these results, it can be concluded that the development of Android-based Physics learning media with the MIT APP Inventor on the subject of static fluids has an assessment with an